Phytocemical Screening and Toxicity Test of Ethanolic Extracts Phanera semibifida (Roxb.) Benth. Stem and Leaves from West Sumatra - Suhendra, Meyla; Fitmawati; Anisa, Nur; Kurnia, Hersan Bayu (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2024)
Indonesian people use plants as medicine because they are considered to have fewer side effects. Phanera semibifida (Roxb.) is a climbing plant that has been used by the community to make therapeutic drugs. Phanera semibifida, especially species in western Sumatra, lacks information on phytochemical composition and toxicity capabilities. So the purpose of this study was to determine the phytochemical content, toxicity (BSLT), and biological activity of Phanera semibifida growing in western Sumatra. The BSLT approach was used in this study to conduct phytochemical screening and toxicity studies on leaves and stems. Phytochemical results were negative for alkaloids and steroids but positive for flavonoids, tannins, saponins, and terpenoids. Based on the BSLT experiment, it can be concluded that both ethanol extracts are highly toxic and show anticancer properties